Diversification of Processed Onion Products as the Iconic Product in Darurejo Village, Jombang Regency - Silvana Dwi Nurherdiana; Reva Edra Nugraha; Rachmad Ramadhan Yogaswara; Handi Ramadhan; Muhammad Hakam; Wahyu Arif Dharmawan (Future Science, 2021)
Darurejo Village, Plandaan District, Jombang is an onion horticulture area where the highest productivity level is in the Jombang Regency of 3990 kw and 38 kw/ha. However, the onion sales are not optimal so farmers often experience losses. Therefore, we service activities regarding the processing and management to enhance the effectiveness. Coinciding with the COVID-19 pandemic and the enactment of the government's decision to Implement Emergency Community Activity Restrictions (ECAR) the implementation of counseling is carried out online. The online activity was carried out through the WhatsApp Group, on Saturday, July 31, 2021, from 11.00-14.00 WIB, which was attended by 25 village cadres. This outreach activity was carried out by providing 2 materials, including basic knowledge of onion and the resulting products such as fried onion, onion baceman, and onion powder which have great potential to be widely sold, and the introduction of automatic peeling machines to increase the quantity and quality of productions through online and offline meeting on August 28, 2021. It is hoped that the community will be able to process and manage the onion shallot potential products.